Tindak Pidana Pembunuhan dan Pemerkosaan di Bawah Pengaruh Minuman Beralkohol oleh Anak di Bawah Umur - Sutrisno, Rekhaf Herdiana (Proceedings Series on Social Sciences & Humanities, 2024)
In essence, children cannot choose or ask who their parents are, how they live. Therefore, parents must give the best to their children so that the future, the journey to success is easy. success becomes easy. In the current era of globalization, the role of parents is very important. very important because in the current era the role of parents is very, very little so that they cannot provide good learning to children, therefore children are very easy to fall into Therefore, children are very easy to fall into promiscuity. Where alcoholic beverages alcohol, sexual harassment and bullying become very, very commonplace and it is always said that it is just a joke. always said that it is just a joke. Our country is a country of law, where all behaviors and ways of treating others are regulated and there are also There are also norms in society that are still very strong. Crimes that occur due to the influence of alcoholic beverages, there is no law in Indonesia that regulates this that regulates it, so that people who commit criminal acts under the influence of alcohol are considered conscious in committing legal acts. under the influence of alcohol are considered conscious in committing the legal act and are subject to Article 340 of the Indonesian Criminal Code. imposed under Article 340 of the Criminal Code while rape is imposed under Article 285 of the Criminal Code. KUHP.